INTERVENSI BERBASIS FARMASI PADA PASIEN DIABETES MELLITUS TIPE 2: TINJAUAN SISTEMATIS: Pharmaceutical Care-Based Interventions in Type 2 Diabetes Mellitus: A Systematic Review - Yusnita Julyarni Akri; Diny Puspitasari (Forind Press, 2024)
The role of pharmacists in diabetes management, including patient identification, assessment, counseling, referral, and monitoring is indispensable. The practice of pharmaceutical services requires pharmacists to carry out their responsibilities. Patient counseling is not only given at initial care at the time primary care is diagnosed, but also at ongoing care management. This study aimed to systematically review pharmaceutical-based interventions in type 2 diabetes mellitus patients. The literature search will be conducted in February 2024. A systematic review is done by searching for articles from Google Scholar. Keywords to search for this article include